Psychosocial Factors Associated with Depressive Symptom Severity among Indonesian Adults: An Ordinal Logistic Regression Analysis of IFLS-5 Data - Ghea Weisha; Mutia Yollanda; Yudiantri Asdi (Counseling and Humanities Review, 2026)
Depression is a major public health concern and one of the most prevalent mental health disorders in Indonesia. However, evidence regarding psychosocial factors associated with depressive symptom severity among Indonesian adults remains limited. This study examined the associations of educational attainment, marital status, and emotional problems with depressive symptom severity using data from the fifth wave of the Indonesia Family Life Survey (IFLS-5). A cross-sectional analysis was conducted among 21,416 adults using descriptive statistics, Chi-square tests, and ordinal logistic regression. The results showed that educational attainment, marital status, and emotional problems were significantly associated with depressive symptom severity. Higher educational attainment and being married were associated with lower odds of more severe depressive symptoms, whereas emotional problems were associated with higher odds. These findings underscore the importance of psychosocial factors in developing targeted mental health interventions for Indonesian adults.